Grado de dimorfismo en la morfometría del seno maxilar, en una muestra de población colombiana (2022)
Introduction: the estimation of sex is an important parameter in the identification of a corpse, therefore the most dimorphic structures should be sought to study their degree of dimorphism and their contribution to research. Objective: to determine the degree of sexual dimorphism of the morphometry of the maxillary sinuses in lateral skull radiographs in a sample of Colombian individuals.